Adenosine-Induced Atrial Fibrillation: Localized Reentrant Drivers in Lateral Right Atria due to Heterogeneous Expression of Adenosine A1 Receptors and GIRK4 Subunits in the Human Heart. Issue 6 (9th August 2016) - Li, Ning; Csepe, Thomas A.; Hansen, Brian J.; Sul, Lidiya V.; Kalyanasundaram, Anuradha; Zakharkin, Stanislav O.; Zhao, Jichao; Guha, Avirup; Van Wagoner, David R.; Kilic, Ahmet; Mohler, Peter J.; Janssen, Paul M. L.; et al.
Abstract : Background: Adenosine provokes atrial fibrillation (AF) with a higher activation frequency in right atria (RA) versus left atria (LA) in patients, but the underlying molecular and functional substrates are unclear. We tested the hypothesis that adenosine-induced AF is driven by localized reentry in RA areas with highest expression of adenosine A1 receptor and its downstream GIRK (G protein-coupled inwardly rectifying potassium channels) channels ( I K, Ado ). Methods: We applied biatrial optical mapping and immunoblot mapping of various atrial regions to reveal the mechanism of adenosine-induced AF in explanted failing and nonfailing human hearts (n=37). Results: Optical mapping of coronary-perfused atria (n=24) revealed that adenosine perfusion (10–100 µmol/L) produced more significant shortening of action potential durations in RA (from 290±45 to 239±41 ms, 17.3±10.4%; P <0.01) than LA (from 307±24 to 286±23 ms, 6.7±6.6%; P <0.01). In 10 hearts, adenosine induced AF (317±116 s) that, when sustained (≥2 minutes), was primarily maintained by 1 to 2 localized reentrant drivers in lateral RA. Tertiapin (10–100 nmol/L), a selective GIRK channel blocker, counteracted adenosine-induced action potential duration shortening and prevented AF induction. Immunoblotting showed that the superior/middle lateral RA had significantly higher adenosine A1 receptor (2.7±1.7-fold; P <0.01) and GIRK4 (1.7±0.8-fold; P <0.05) protein expression than lateral/posterior LA. Conclusions: This study revealed a 3-fold RA-to-LA adenosine A1 receptor protein expression gradient in the human heart, leading to significantly greater RA versus LA repolarization sensitivity in response to adenosine. Sustained adenosine-induced AF is maintained by reentrant drivers localized in lateral RA regions with the highest adenosine A1 receptor/GIRK4 expression. Selective atrial GIRK channel blockade may effectively treat AF during conditions with increased endogenous adenosine. Abstract : Supplemental Digital Content is available in the text.